Pengetahuan Ekologis Tradisional, Kearifan Lokal, Dan Pengelolaan Lingkungan - Leni Agrariani (CV. SINAR HOWUHOWU, 2026)
Traditional ecological knowledge represents a body of knowledge developed through long-term interactions between local communities and their natural environment. This knowledge encompasses values, norms, and practices that play a significant role in environmental management based on local wisdom. This study aims to examine the role of traditional ecological knowledge in supporting sustainable environmental management. The research employs a qualitative descriptive approach, with data collected through in-depth interviews, participant observation, and documentation studies. The research participants include customary leaders and community members directly involved in local environmental management practices. Data analysis was conducted thematically through data reduction, data display, and conclusion drawing. The findings indicate that traditional ecological knowledge serves as a fundamental guideline for sustainable natural resource utilization, strengthens social cohesion, and helps maintain ecological balance. However, modernization and social change pose significant challenges to the preservation of this knowledge. Therefore, integrating traditional ecological knowledge into modern environmental policies and strengthening the role of local communities are strategic steps toward achieving sustainable environmental management.